Psychological Factors and Organizational Factors on Employee Performance - Zaeni, Nurhaeda; Kitta, Syafruddin (Jurnal Manajemen Bisnis, 2023)
This research is a type of Quantitative research that aims to determine the influence and analyze how the influence of Psychological and Organizational Factors on Employee Performance at the Class 1A Sungguminasa District Court Office in Gowa Regency. The independent variables in this study are Psychological Factors and Organizational Factors while the dependent variable is Employee Performance. The number of respondents in this study was 70 employees at the Sungguminasa District Court Office Class 1A in Gowa Regency. Research data were obtained using Observation, Interview, Documentation, and Questionnaire Techniques. The data analysis methods used are descriptive analysis tests, research instrument tests (validity tests and reliability tests), multiple linear regression analysis tests, hypothesis tests (t tests, f tests, correlation coefficient tests, and determination coefficient tests. The results of this study show that Psychological Factors partially have a positive and significant effect on Employee Performance, Organizational Factors partially have a positive but not significant effect on Employee Performance, and Psychological Factors and Organizational Factors together or simultaneously affect Employee Performance at the Sungguminasa District Court Office Class 1A in Gowa Regency